Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Gapura Angkasa Di Bandar Udara Internasional Sultan Mahmud Badaruddin II Palembang - Ryan Dynata; Gallis Nawang Ginusti (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
The service of an aircraft on the ground at the airport is handled by the Ground Handling unit. One of the ground handling companies at the airport International Sultan Mahmud Badaruddin II Palembang is PT Gapura Angkasa. PT Gapura Angkasa is engaged in providing Ground Handling services for airlines operating in Indonesia. One of the factors that support organizational culture is one of the factors that is strong and supports performance development is organizational culture Another factor that affects the performance of PT Gapura Angkasa employees is work discipline, because discipline is a form of training for the company. This study aims to determine how the influence of organizational culture and work discipline on the performance of PT Gapura Angkasa employees at Sultan Mahmud Badaruddin II International Airport Palembang. The method used in this study is quantitative method. A sample of 95 employees. The population in this study consisted of employees of PT. The gate at Sultan Mahmud Badaruddin II International Airport Palembang is as many as 95 population. The sampling technique used is the Nonprobability Sampling technique, which is a sampling technique that does not provide equal opportunities or opportunities for every element or member of the population to be sampled.The data collection technique was carried out by distributing questionnaires which were carried out in September 2023. Data analysis techniques used include validity tests, reliability tests, simple linear regression tests, determination coefficient tests, T tests, and F tests. The results showed that partially organizational culture and work discipline affect performance. The higher the organizational culture and work discipline, the higher the performance. Simultaneously, organizational culture and work discipline have a positive and significant effect on employee performance. This can be seen from the significant value of 0.000 less than 0.05 and the results of multiple linear tests show a constant value (a) marked negative, which is 3.356 meaning that if organizational culture, work discipline and performance are equal to zero (0) then employee performance decreases; From the results of coefficient determination, the R square number is 0.813 or 81.3%. This explains that the relationship between organizational culture variables and work discipline has a very strong correlation.